Code-Switching as a Countenance of Language Interference inTeacher’s Talk - Jahan, Kalsoom; Ashraf, Shumaila; Shakir, Aleem; Mushtaq, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the functions of code-switching in teacher’s talk in an ELT classroom. It was aimed to identify the functions of code-switching in language classroom and to estimate the use of Urdu and English languages in ELT classroom in Lahore. The major functions of code-switching has been identified by using the framework of Hymes (1962), Mehan (1979) Sinclair and Brazil (1982). It was a case study, a video lecture by a renowned English teacher “Syed Ejaz Bukhsri” was downloaded from YouTube. This video lecture by Syed Ejaz Bukhari was delivered at Aspire College Manawan, Lahore. The lecture included in the study was related to the speaking skills. Teacher used both languages L1 and L2 during the lecture. He used L1 more than L2 while teaching speaking skills to his students. Most of the time he explained the concepts in Urdu language and used code-switching for questioning, inviting, expressing, directing, practicing, informing, persuading, encouraging, and commenting.